A case control study: to evaluate the lipid profile in ischemic and hemorrhagic stroke - Sharma, Chandan; Badyal, Ashima (International Journal of Scientific Reports, 2021)
Background: Stroke, be it ischemia or hemorrhage, is the most common clinical manifestation of cerebrovascular disease of which more than 99% are due to arterial involvement and less than 1% due to venous involvement. The aim of the present study was to assess the lipid profile of patients with ischemic and hemorrhagic stroke and to compare it with control group. Methods: This study was conducted in the Department of Medicine in collaboration with Department of Biochemistry between February 2018 to August 2018 on 50 patients of infarct and 50 patients of hemorrhagic stroke admitted in GMC Jammu and 50 healthy controls. Serum was analyzed for estimation of serum lipid profile including total cholesterol, triglyceride, high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), by using fully automatic analyzer. Results: More than 54% of patients and controls belonged aged more than 60 years, with a total of 81 males and 69 females. Mean values of total cholesterol (233.53±27.09 mg) and LDL (165.89±30.54 mg) showed up higher in hemorrhagic stroke patients however higher mean values of triglycerides (177.80±40.44 mg) showed up in ischemic stroke patients. Serum cholesterol was abnormal among 50% ischemic and 54% hemorrhagic patients. A significant association is found between raised cholesterol, LDL, abnormal HDL and ischemic stroke. Conclusions: A significant rise in total cholesterol level was found in case of both the groups, therefore high risk patients with stroke should be regularly screened for serum lipid profile.